A Redox Tale of Two Phosphine Oxides (and a Terthiophene) - Käch, Daniel; Bezdek, Máté J. (Synlett, 2024)
Despite the appeal of organic redox systems as next-generation energy-storage media, achieving high cell voltages with electrolytes based on main-group elements typically comes at the cost of reduced long-term stabilities. In this Synpacts article, we summarize our recent finding that the introduction of phosphine oxide functionalities can unlock the ability of terthiophenes to serve as robust two-electron acceptors at extreme potentials. These investigations uncovered a fundamentally new class of multielectron redox systems, capable of expanding the cell potential range achievable with organic electrolytes without compromising stability.
Keywords: redox chemistry; main-group radicals; energy storage; electrochemistry; terthiophenes; phosphine oxides